Rebranding Inpatient Community Meetings - Hannah Campling; Bharat Velani; Georgina Hearn (BJPsych Open, 2025)
Aims: The North London Foundation Trust was established in 2024. The partnership has created a new clinical strategy for the next 5 years (2024–2029) and some of the main priorities are: “For all services to use a trauma informed approach”, “Service users must be involved in co-production and decision making”, “Value feedback from service users”, “Facilitate communication and information sharing with service users”.